1973
DOI: 10.1111/j.0022-3646.1973.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH OF THE GREEN ALGA CODIUM FRAGILE IN A CONNECTICUT ESTUARY1

Abstract: SUMMARY An in situ comparison of environmental and physiological factors was undertaken in 1971–72 (15 months) in the Niantic River estuary to elucidate some of the important aspects, of the growth and development of the seaweed Codium fragile. In general, Codium in the estuary has a growing season of from 6 to 9 months. Growth increments during this period are relatively constant. Temperature and salinity are the main limiting factors to growth, although low summer concentrations of inorganic nitrogen may als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…G. vermculophylla had high performance at all sites, matching its wide distribution in Hog Island Bay ) and supporting the view of this species as being highly stress tolerant (Yokoya et al 1999;Wallentinus et al 2004;Rueness 2005). In contrast, C. fragile showed poor performance at near-mainland sites despite a reported tolerance to high nutrients, low salinity and low light (Malinowski and Ramus 1973;Hanisak 1979a;Trowbridge 1998), suggesting that invasions are unlikely in these locations. The native species often also had low performance at the near-mainland sites, indicating generally poor growth conditions.…”
Section: Distance Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…G. vermculophylla had high performance at all sites, matching its wide distribution in Hog Island Bay ) and supporting the view of this species as being highly stress tolerant (Yokoya et al 1999;Wallentinus et al 2004;Rueness 2005). In contrast, C. fragile showed poor performance at near-mainland sites despite a reported tolerance to high nutrients, low salinity and low light (Malinowski and Ramus 1973;Hanisak 1979a;Trowbridge 1998), suggesting that invasions are unlikely in these locations. The native species often also had low performance at the near-mainland sites, indicating generally poor growth conditions.…”
Section: Distance Gradientmentioning
confidence: 99%
“…80% of the total biomass (earlier identified as G. verrucosa, Thomsen 2004a, b;. C. fragile and G. vermiculophylla have both been described as successful invaders of shallow turbid lagoons and estuaries (Fralick and Mathieson 1973;Malinowski and Ramus 1973;Carlton and Scanlon 1985;Trowbridge 1998;Rueness 2005), a notion supported by their dominance in Hog Island Bay. We therefore expected the two aliens to have superior performance under conditions typical of such ecosystems, including low light availability due to high water column turbidity Lawson 2003), high mesograzer densities (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Reproduction of Codium fragile involves fragmentation (Fralick and Mathieson 1972), drifting of entire plants (Moeller 1969) and production of motile reproductive cells (Malinowski and Ramus 1973). On the Pacific coast of North America (Borden andStein 1969), in Japan (Arasaki et al 1955) and in Australia (Williams 1925) C. fragile produces anisogametes with the zygote germinating into erect thalli.…”
mentioning
confidence: 99%
“…However, the prediction of such an extreme outcome does not consider factors that can limit the impacts of dense Codium beds. Codium has been suggested to be excluded by shading and increased sedimentation in dense eelgrass stands (Malinowski and Ramus 1973). Sparse seagrass beds may thus be more susceptible to invasion by macroalgae as they create physical conditions that facilitate macroalgal growth (Ceccherelli and Cinelli 1999) (c) Fig.…”
Section: Experiments Versus Patterns In Natural Invaded Bedsmentioning
confidence: 99%
“…Although typically associated with hard substrates, including both rocky substrata and shells, this large seaweed is also able to epiphytically colonize exposed seagrass rhizomes (Garbary et al 2004), growing as long as or longer than the plants with which it is associated (authors, personal observations). Earlier studies suggested that Codium was a poor competitor for resources with native seagrass in soft-bottom habitats, due in part to the limited availability of hard substrata (Malinowski and Ramus 1973) and a greater vulnerability to environmental conditions in lagoonal systems relative to native algae (Thomsen and McGlathery 2007). However, Codium is tolerant to estuarine conditions (Kim and Garbary 2007), and its ability to grow directly on eelgrass rhizomes gives it the potential to develop dense populations in soft-bottom habitats.…”
Section: Introductionmentioning
confidence: 99%